Using tax incentives to compete for foreign investment : are they worth the costs - Wells, Louis T.; Allen, Nancy J.; Morisset, Jacques; Pirnia, Neda (Washington, D.C. : The World Bank, 2001)
Business
Keywords: Foreign investment; Tax incentives; Foreign investment